The Corn Development Strategy in Peat Soil With No Burning and Traditional Methods - Selmitri, Selmitri; Yurisinthae, Erlinda; Radian, Radian (Universitas Bangka Belitung, 2020)
The study aims to analyze the differences in the development of corn cultivation in peat soils between no-burning and traditional methods or with burning in Rasau Jaya District, Kubu Raya District. The fact that currently clearing forests is still using burning on agricultural land in general and especially on peat soil that is feared to experience underground burning is difficult to overcome and cause many losses. The development of corn on land without burning on peat soil is a solution for the community in maintaining ecosystem sustainability. The explanatory research is directed at testing hypotheses and following research objectives. Data collection by interview and questionnaire to 60 respondents were corn farmers on peat soil. The average difference test is used in explaining the difference in yield between the two methods of planting on peat soil. The results found that there were significant differences in the application of corn cultivation on peat soil without burning compared to the traditional method on the variables fertilizer, pesticide, business costs, and yields. In contrast, the planting area variable had no significant difference.